The IVF-LUBE trial – a randomized trial to assess Lipiodol® uterine bathing effect in women with endometriosis or repeat implantation failure undergoing IVF. Issue 3 (March 2019) - Reilly, Shelley J; Glanville, Elizabeth J; Dhorepatil, Bharati; Prentice, Lucy R; Mol, Ben W; Johnson, Neil P
Abstract: Research question: Does pre-IVF Lipiodol® increase the success of IVF treatment in women with endometriosis or repeat implantation failure (RIF) compared with IVF alone? Design: Lipiodol is known to enhance natural fertility, especially amongst women with endometriosis. The effect of Lipiodol may accrue through an impact on the endometrium that enhances receptivity to implantation. A randomized controlled trial (RCT) was carried out on 70 women due to undergo IVF. Women with endometriosis or RIF in previous IVF treatments, recruited from IVF clinics in New Zealand and in Pune, India, received either Lipiodol by hysterosalpingogram or no intervention prior to IVF treatment. Results: Between May 2009 and January 2014, 33 women were randomized to Lipiodol plus IVF and 37 to IVF alone. When pregnancies resulting from fresh embryo transfer from the IVF cycle under study were considered, live birth rates were 8/33 (24%) in the pre-IVF Lipiodol group and 11/37 (30%) in the IVF only group (relative risk [RR] 0.81; 95% confidence interval [CI] 0.37 to 1.8). Live birth rates from pregnancies within 6 months were 11/33 (33%) and 12/37 (32%) in these respective groups (RR 1.03; 95% CI, 0.53 to 2.0). The trial was underpowered to detect smaller differences between treatment and control groups. Conclusions: No evidence was found of benefit of Lipiodol prior to fresh embryo transfer in women with endometriosis or RIF. It is suggested that this treatment should not be undertaken purely as an adjuvant in IVF other than in the context of a further well-designed RCT.